PENGARUH PENERAPAN e-SPT TERHADAP EFISIENSI PEMROSESAN DATA PERPAJAKAN (Survey Terhadap Pengusaha Kena Pajak pada KPP Pratama Kota Tomohon) - Mokolinug, Debbie Deborah. S.; Budiarso, Novi S. (Universitas Sam Ratulangi, 2015)
Breakthroughs related to the application of Information Technology in taxation activity continues to be done in order to facilitate, improve and optimize the service to taxpayers. There are many factors that influence the success of applied information technology. It is associated with a recent study also analyzes the success of information technology established by the Directorate General of Taxation (DGT) is an e-SPT This study was conducted to verify the success of e-SPT system used by employers taxable. The purpose of this study was to determine the effect of practicality, ease of calculation, the ease of reporting and reliability of e-tax return on tax data processing efficiency. The analytical method used is multiple regression analysis. The results showed that the practicality and ease of calculation significantly affect the efficiency of data processing tax on taxable employers in Tomohon while reporting the ease and convenience of e-SPT does not significantly affect the efficiency of data processing tax on taxable employers in Tomohon